Identification of mimotopes of Mycobacterium leprae as potential diagnostic reagents - Alban, Silvana M (BioMed Central, 2013)
BACKGROUND: An early diagnostic test for detecting infection in leprosy is fundamental for reducing patients’ sequelae. The currently used lepromin is not adequate for disease diagnosis and, so far, no antigen to be used in intradermoreaction has proved to be sensitive and specific for that purpose. Aiming at identifying new reagents to be used in skin tests, candidate antigens were investigated. METHODS: Random peptide phage display libraries were screened by using antibodies from leprosy patients in order to identify peptides as diagnostic reagents. RESULTS: Seven different phage clones were identified using purified antibodies pooled from sera of leprosy patients. When the clones were tested with serum samples by ELISA, three of them, 5A, 6A and 1B, allowed detecting a larger number of leprosy patients when compared to controls. The corresponding peptides expressed by selected phage clones were chemically synthesized. A pilot study was undertaken to assess the use of peptides in skin tests. The intradermal challenge with peptides in animals previously sensitized with Mycobacterium leprae induced a delayed-type hypersensitivity with peptide 5A (2/5) and peptide 1B (1/5). In positive controls, there was a 3/5 reactivity for lepromin and a 4/5 reactivity of the sensitized animals with soluble extract of M. leprae. CONCLUSIONS: The preliminary data suggest that may be possible to develop reagents with diagnostic potential based on peptide mimotopes selected by phage display using polyclonal human antibodies.